Review of skin cancers terminology, etiology and treatment from ancient Persian medicine view point - Maryam Iranzadasl; Parvin Mansouri; Mohammad Kamalinejad; Narjes Gorji (Institue of Medicinal Plants, ACECR, 2020)
Background: Skin cancers are the most prevalent type among the white with an increasing trend of incidence around the world and Iran. Scientific developments in diagnosing these cancers and using screening methods and utilizing treatment methods have contributed to the relative control of the cancer. Hence, it is necessary to consider other suggested approaches of complementary and traditional medicine to prevent and treat these cancers. Objective: The purpose of this review is to investigate the alternative remedies from the Persian Medicine; as a pioneer medical approach with an old history. Methods: In this review study, the medical textbooks of the golden era of Persian Medicine (9th to 19th centuries AD), i.e., the times of Razes and Avicenna, were explored and interesting opinions on skin malignancies were found. In addition, the phrase "skin cancers" was searched in databases like PubMed, Science Direct, Scopus, and Google Scholar. The gleaned data were analyzed and compared. Results: The ancient Persian scholars knew the cancers and were forerunners in the description, classified, etiology and treatment of skin cancers. This study explored interesting opinions like nutrition and black bile clearance on skin malignancies  treatment, also found no contradictory views between the Persian and modern medicine on the topic of skin cancers. Conclusion: Paying attention to the neglected areas can makes useful theories and hypotheses fore achievement to new more effective and safe remedies.